Cumulative cortisol concentrations in hair of patients with atopy are lower than in healthy subjects and are not related to their perceived stress experience. (1st November 2020) - Solarikova, P.; Karailievova, L.; Rajcani, J.; Brezina, I.; Jezova, D.
Abstract: Patients with atopy were found to exhibit blunted cortisol responses to acute stress stimuli. The aim of this study was to test the hypothesis that cumulative cortisol concentrations in the hair of patients with atopy are lower than in healthy subjects when related to their perceived stress experience. The sample consisted of 31 participants. The most proximal 3 cm of hair (as close to the scalp as possible), reflecting the cumulative cortisol secretion during the previous 3 months, was used for the analysis. Only in 20 subjects (9 patients with atopy and 11 healthy controls), there was a sufficient amount of hair for precise analysis using a new methodology. The results showed lower hair cortisol concentrations in patients with atopy compared to those in controls. The perceived stress scores in patients with atopy and healthy controls were not statistically different. The cortisol concentration/perceived stress score ratios were lower in patients with atopy compared to those in controls. No statistically significant correlation between hair cortisol and long-term experienced stress assessed via perceived stress scale was observed. In conclusion, the cumulative cortisol secretion in the hair of atopic patients is lower than would be expected according to their subjective scores of perceived stress. Most importantly, the previously lower stress hormone increase found in acute stress situations and in children now was confirmed in adult patients with chronic stress load.